Upaya Peningkatan Pendapatan Keluarga Melalui Usaha “ Bandeng Presto” - - Sulistyowati; Totok Sumaryanto; Danang Dwi Saputro; - Sunyoto (Universitas Katolik Soegijapranata, 2021)
The purpose of IbW activities is to solve problems faced by the community (KUB Putri Tirang) whose efforts are not carried out continuously. Implementation Method: 1) Through the process of counseling, training and mentoring at the house of the chairman of the bandeng Group Presto